Application Prospect of Roof Greening in Sponge City - LUO Pingping; LIU Jiaxin; SU Mengfei; CAI Haohan; JIE Yuhan; LI Lingyu; ZHOU Meimei; LYU Jiqiang; SHI Wenhai (Renmin Zhujiang)
In recent years, the frequency and intensity of urban flood are increasing day by day.The construction of “Sponge city” with naturalaccumulation, penetration and purification provides a direction for the development of roofgreening, that is roof greening transformation based on sponge city. This paper mainly summarizesthe status and development of roof greening. By analyzing the functions of roof greening, such aswater storage capacity and rainwater interception capacity, it points out that roof greening playsa positive role in reducing the urban surface runoff coefficient, reducing the peak flow, andrelieving the load pressure of urban drainage network, so as to achieve the purpose of alleviatingurban inundation. At the same time, it also discusses that the roof greening has a broadapplication prospect in improving the related fields of urban environmental ecology and spongecity construction. In addition, this paper analyzes the current challenges of roof greening, putsforward suggestions and relevant solutions in terms of technology and management, and providesrelevant technical guidance for the construction of sponge city in the future.